Effect of heat stress on meat quality: A review - Mia, N; Rahman, MM; Hashem, MA (Meat Research, 2023)
One of the stressful situations for livestock and poultry is heat stress (HS), which has a detrimental effect on animal physiology, production, and product quality. Because of their quick development and metabolism, high production, and species-specific characteristics including decreased sweating, the protective layer of skin, and rumen fermentation, some varieties of livestock are more vulnerable to heat stress than others. Muscle that is pale, soft and exudative (PSE) and lacks the ability to retain water can be produced by short-term heat stress that occurs pre-slaughter. This stress increases muscle glycogenolysis. In contrast, animals that experience prolonged heat stress have lower muscle glycogen reserves, which results in meat that is dark, firm, and dry (DFD), has a high final pH and water retention capacity. Moreover, HS causes shortened shelf life, oxidative stress. According to a recent study, HS might plausibly modify the rate and amount of postmortem muscle glycolysis and the resulting pH, which can impact the physiological and metabolic disturbances that occur in live animals as well as the features of carcasses and meat quality. This review reflects the effect of heat stress on meat quality.